Data from: Intercontinental genetic structure and gene flow in Dunlin (Calidris alpina), a potential vector of avian influenza - Miller, Mark P.; Haig, Susan M.; Mullins, Thomas D.; Ruan, Luzhang; Casler, Bruce; Dondua, Alexei; Gates, H. River; Johnson, J. Matthew; Kendall, Steve; Tomkovich, Pavel S.; Tracy, Diane; Valchuk, Olga P.; et al. (2014)
Waterfowl (Anseriformes) and shorebirds (Charadriiformes) are the most common wild vectors of influenza A viruses. Due to their migratory behavior, some may transmit disease over long distances. Migratory connectivity studies can link breeding and nonbreeding grounds while illustrating potential interactions among populations that may spread diseases. We investigated Dunlin (Calidris alpina), a shorebird with a subspecies (C. a. arcticola) that migrates from nonbreeding areas endemic to avian influenza in eastern Asia to breeding grounds in northern Alaska. Using microsatellites and mitochondrial DNA, we illustrate genetic structure among six subspecies: C. a. arcticola, C. a. pacifica, C. a. hudsonia, C. a. sakhalina, C. a. kistchinski, and C. a. actites. We demonstrate that mitochondrial DNA can help distinguish C. a. arcticola on the Asian nonbreeding grounds with >70% accuracy depending on their relative abundance, indicating that genetics can help determine if C. a. arcticola occurs where they may be exposed to highly pathogenic avian influenza (HPAI) during outbreaks. Our data reveal asymmetric intercontinental gene flow, with some C. a. arcticola short-stopping migration to breed with C. a. pacifica in western Alaska. Because C. a. pacifica migrates along the Pacific Coast of North America, interactions between these subspecies and other taxa provides route for transmission of HPAI into other parts of North America. mtDNA and microsatellite_dataA zip file containing two data files plus a third text file containing descriptions of the data files. See file "File annotations.txt" included int the archive for more information.